KUALITAS PELAYANAN DAN KEPUASAN: PERSEPSI MAHASISWA PROGRAM STUDI MANAJEMEN UNIVERSITAS KLABAT - Wahongan, Moody (JBE (Journal of Business and Economics); Volume 12 No.1, 2013 JBE UNKLAB, 2013)
This descriptive survey aimed to obtain the students’ perceptions of the service quality that included tangibles, reliability, responsiveness, assurance, emphaty and the satisfication towards the service quality in the Management program at Universitas Klabat.  The data was obtained through questionnaires from 89 students who were enrolled in Semester II, 2011/2012, but only 80 questionnaires were used due to the technical reasons.  Based on the descriptive and inferential analysis, the following results were obtained:  (1) In general, the students’ perceptions of the service quality in the Management program were good, (2) In general, the students’ perceptions of the satisfaction towards the service quality were satisfactory, and (3) There was significant correlation between the students’ perceptions of the service quality and their satisfaction level.  It was concluded that even though the results show mean scores of good and satisfactory, the service quality had not been done in a maximum way; therefore, the recommendation given was to maximize the overall service quality especially on the aspects that received low score such as the internet access